Zero Morphology and the T/SM Restriction in the L2 Acquisition of Psych Verbs - White, Lydia; Montrul, Silvina; Hirakawa, Makiko; Chen, Dongdong; Bruhn de Garavito, Joyce; Brown, Cynthia (MORPHOLOGY AND ITS INTERFACES IN SECOND LANGUAGE KNOWLEDGE, Beck, Maria-Luise [Ed], Amsterdam: John Benjamins, 1998, pp 257-282, 1998)
Whether second-language (L2) learners of English acquire syntactic properties connected to the zero causative morpheme in the case of T/SM (target/subject matter of emotion) verbs (eg, fear & frighten) was investigated using a scalar judgment task with three groups of learners: native speakers of Spanish, French, & Malagasy (N = 17, 15, & 19 adults, respectively). Subjects (Ss) were asked to rate the grammatical acceptability of sentences with T /SM-Causer violations & make + frighten-type predicates (eg, *Toby frightened the squirrels of his teeth & Toby made the squirrels frightened of his teeth) & to sentences with Causer subjects (eg, Toby frightened the squirrels) & ungrammatical frighten-type predicates in which the violation involved something other than thematic properties (eg, word order). Results showed that all S groups were sensitive to the grammaticality of sentences with Causer subjects & the ungrammaticality of sentences with violations unrelated to thematic properties. However, whereas native-English-speaking controls & Malagasy L2 English learners judged the sentences with T/SM-Causer violations as ungrammatical, the Spanish speakers judged them as grammatical. Several possible interpretations for the findings are discussed, with emphasis on the hypothesis that Romance speakers could be interpreting these sentences as eventive rather than stative. Implications of these results for D. Pesetsky's (1995) zero syntax theory are also discussed. 1 Table, 7 Figures, 25 References. C. Brennan